„Always was and always will be, that a man will sleep with another man’s wife“: „Alternative“ sexual morals and their control in the inquisitional register of Jacques Fournier - Zbíral, David (Dějiny – teorie – kritika, 2008)
The inquisitorial register of Jacques Fournier, from 1318–25, well known thanks to Montaillou (1975) by Emmanuel Le Roy Ladurie, reaches far beyond the topic of heresy. It encompasses various details about everyday life, including sexuality and more or less ‘alternative’ sexual mores. The analysis of four cases recorded in the register – those of Beatrix of Lagleize, Peter Vidal, Arnold of Verniolles, and Grazida Lizier – not only shows their interesting systems of ethics, but also points to more general matters of method. In this case study, the norm-deviation model displays all its weakness. The sexual mores of these four people are certainly different from the morals required by Fournier, and they form independent systems rather than simple deviations from “official” morals. By its distribution of power and its focus, the norm-deviation model overstates the unity of medieval Christianity.